DNA Repair Protein APE1 Degrades Dysfunctional Abasic mRNA in Mitochondria Affecting Oxidative Phosphorylation. Issue 18 (3rd September 2021) - Barchiesi, Arianna; Bazzani, Veronica; Jabczynska, Agata; Borowski, Lukasz S.; Oeljeklaus, Silke; Warscheid, Bettina; Chacinska, Agnieszka; Szczesny, Roman J.; Vascotto, Carlo
Graphical abstract: Abstract: APE1 is a multifunctional protein which plays a central role in the maintenance of nuclear and mitochondrial genomes repairing DNA lesions caused by oxidative and alkylating agents. In addition, it works as a redox signaling protein regulating gene expression by interacting with many transcriptional factors. Apart from these canonical activities, recent studies have shown that APE1 is also enzymatically active on RNA molecules. The present study unveils for the first time a new role of the mitochondrial form of APE1 protein in the metabolism of RNA in mitochondria. Our data demonstrate that APE1 is associated with mitochondrial messenger RNA and exerts endoribonuclease activity on abasic sites. Loss of APE1 results in the accumulation of damaged mitochondrial mRNA species, determining impairment in protein translation and reduced expression of mitochondrial-encoded proteins, finally leading to less efficient mitochondrial respiration. Altogether, our data demonstrate that APE1 plays an active role in the degradation of the mitochondrial mRNA and has a profound impact on mitochondrial well-being.